PARP-Targeted Auger Therapy in p53 Mutant Colon Cancer Xenograft Mouse Models - Wilson, Thomas; Pirovano, Giacomo; Xiao, Gu; Samuels, Zachary; Roberts, Sheryl; Viray, Tara; Guru, Navjot; Zanzonico, Pat; Gollub, Marc; Pillarsetty, Naga Vara Kishore; Reiner, Thomas; Bargonetti, Jill (Molecular pharmaceutics, 2021)
Despite Auger electrons being highly appealing due to their short-range and high linear energy transfer to surrounding tissues, the progress in the field has been limited due to the challenge in delivering a therapeutic dose within the close proximity of cancer cell's DNA. Here, we demonstrate that the PARP inhibitor I-MAPi is a viable agent for the systemic administration and treatment of p53 mutant cancers. Significantly, minimal off-site toxicity was observed in mice administered with up to 74 MBq of I-PARPi. Taken together, these results lay the foundation for future clinical evaluation and broader preclinical investigations. By harnessing the scaffold of the PARP inhibitor Olaparib, we were able to deliver therapeutic levels of Auger radiation to the site of human colorectal cancer xenograft tumors after systemic administration. In-depth toxicity studies analyzed blood chemistry levels and markers associated with specific organ toxicity. Finally, p53 and p53 human colorectal cancer cell lines were evaluated for the ability of I-MAPi to induce tumor growth delay. Toxicity studies demonstrate that both I-MAPi and its stable isotopologue, I-PARPi, have no significant off-site toxicity when administered systemically. Analysis following I-MAPi treatment confirmed its ability to induce DNA damage at the site of xenograft tumors when administered systemically. Finally, we demonstrate that I-MAPi generates a therapeutic response in p53 , but not p53 , subcutaneous xenograft tumors in mouse models. Taken together, these results represent the first example of a PARP Auger theranostic agent capable of delivering a therapeutic dose to xenograft human colorectal cancer tumors upon systemic administration without causing significant toxicity to surrounding mouse organs. Moreover, it suggests that a PARP Auger theranostic can act as a targeted therapeutic for cancers with mutated p53 pathways. This landmark goal paves the way for clinical evaluation of I-MAPi for pan cancer therapeutics.